Estudio del self en actores profesionales de teatro que representan la violencia política y el conflicto armado en Colombia (2016)
"Theater is confrontation, struggle, movement, transformation, and not only the exhibition of the soul's condition" (Boal, 2001, p.121). With this sentence Augusto Boal, the famous brasilian playwright creator of the Theater of the Oppressed, raises the importance of the political commitment of theater in society, breaking consequently the boundaries of its historic assignment: the artistic representation. Moreover, actors are the ones in charge of interpreting the psychological, emotional, social and physical complexity of other human beings who lived, or live, a specific and different reality. Within the political context of Colombia, most of the plays in theater have looked for a representation of the political violence from the beginning of the armed conflict to our days. Therefore, many actors have had the responsibility of representing victims or soldiers (either from the Colombian army or the revolutionary armed groups), exploring inside each specific context, in order to approach adequately to their realities.